2004
DOI: 10.1126/science.1097830
|View full text |Cite
|
Sign up to set email alerts
|

Selective Growth of Metal Tips onto Semiconductor Quantum Rods and Tetrapods

Abstract: We show the anisotropic selective growth of gold tips onto semiconductor (cadmium selenide) nanorods and tetrapods by a simple reaction. The size of the gold tips can be controlled by the concentration of the starting materials. The new nanostructures display modified optical properties caused by the strong coupling between the gold and semiconductor parts. The gold tips show increased conductivity as well as selective chemical affinity for forming self-assembled chains of rods. Such gold-tipped nanostructures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
1,241
4
17

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,072 publications
(1,293 citation statements)
references
References 26 publications
31
1,241
4
17
Order By: Relevance
“…It is possible that the extra spots on Si(100)/gold result from the presence of crystalline gold silicides (summarized in Table 1, Supporting Information). In Figure 5a for gold on Si(111), there are seven additional spots (in green), of which four can be indexed against the Au 2 Si, Au 5 Si, Au 7 Si intermetallics. In Figure 5b for gold on Si(100), 11 additional spots are observed of which 9 can be indexed for intermetallics, and in Figure 5c, for a different region of gold on Si(100), 12 extra spots are observed of which 7 can be indexed for intermetallics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the extra spots on Si(100)/gold result from the presence of crystalline gold silicides (summarized in Table 1, Supporting Information). In Figure 5a for gold on Si(111), there are seven additional spots (in green), of which four can be indexed against the Au 2 Si, Au 5 Si, Au 7 Si intermetallics. In Figure 5b for gold on Si(100), 11 additional spots are observed of which 9 can be indexed for intermetallics, and in Figure 5c, for a different region of gold on Si(100), 12 extra spots are observed of which 7 can be indexed for intermetallics.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 5b for gold on Si(100), 11 additional spots are observed of which 9 can be indexed for intermetallics, and in Figure 5c, for a different region of gold on Si(100), 12 extra spots are observed of which 7 can be indexed for intermetallics. The spots in the Si(100) case correspond to the following intermetallics: Au 7 Si, Au 4 Si, Au 5 Si, Au 5 Si 2 ,Au 3 Si 2 ,Au 3 Si, and Au 2 Si. Similarly, six extra spots are observed in the diffraction pattern for a gold nanoparticle on a silicon nanowire (Figure 5d), three of which can be indexed to the Au 2 Si, Au 5 Si, and Au 7 Si intermetallics.…”
Section: Resultsmentioning
confidence: 99%
“…Integrating different metallic NCs into a HMNC can introduce new and enhanced properties, or multi-functionality not found in the parent metal NCs [1][2][3][4][5][6][7] . The properties of a HMNC are clearly architecture dependent [7][8][9][10][11][12][13][14][15][16][17] .…”
Section: Spatial Arrangement Edge Satellitementioning
confidence: 99%
“…1,2 The literature now contains several cases with chemical transformations being accompanied by varying degrees of modification of properties, including crystal structure and particle shape. [3][4][5] As a recent example, we demonstrated that as-synthesized metallic nanocrystals yield, upon oxidation, nanostructures with modified morphologies such as hollow particles. 6 This morphological change derives from directional material flows due to differing diffusivities for the reacting atomic species, in a nanoscale version of the well-known Kirkendall Effect.…”
mentioning
confidence: 91%